THE INFLUENCE OF FINANCIAL LITERACY ON STUDENT BEHAVIOR IN MANAGING FINANCIAL KIP-KULIAH SCHOLARSHIP FUNDS - Irpan, Irpan; Nasrullah, Nasrullah; Abdul Khaliq (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to examine the effect of financial literacy on student behavior in managing financial smart Indonesian card scholarship funds (Kip-Kuliah), this study uses quantitative methods, the sample in this study was taken from students receiving smart Indonesian card scholarships (Kip-Kuliah) semester 3, 5, and 7 in the Management study program of the Faculty of Economics and Business, Unismuh Makassar. This research data was obtained from a questionnaire (primary data). The results of research from data processed using SPSS statistical calculations, based on the results of SPSS output partially, the results showed that financial literacy variables have an influence on student behavior in managing the finances of the Smart Indonesia Card scholarship fund (Kip-Kuliah)